PENGARUH MATA PELAJARAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMA NEGERI 1 SUNGAI AMBAWANG - Joni Heriansyah; Rustiyarso Rustiyarso; Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This thesis is titled "The Effect of Entrepreneurship Subjects on Entrepreneurial Interest in High School Students of Sungai Ambawang 1". The general problem in this study is "Knowing the Effect of Entrepreneurship Subjects on Entrepreneurial Interest in SMA Negeri 1 Sungai Ambawang which supports 541 students, samples are taken using a simple random sample of 110 students. Data collection uses direct communication, indirect communication and documentary studies. Research shows there is a difference between the independent variable (X) against the dependent variable (Y) associated with calculations using a simple linear regression equation Y = a + Bx. 1) Entrepreneurship Subjects at Sungai Ambawang 1 High School are included in both categories. This can be seen from the results of research into the way teachers teach in table 4.5 which is as much as 64.1%, including both categories. 2) Entrepreneurial Interest of Ambawang River 1 High School students is good. 3) There is an influence of entrepreneurship subjects on the interest of entrepreneurship students of Sungai Ambawang 1 High School. Obtained by simple linear regression calculations, the equation Y = 33.655 + 0.735X is obtained, which means the constant value is 33.655, if the entrepreneurial subject (X) has a value of 0 (zero), the interest in student entrepreneurship (Y) is 33.665. The significant value of a hypothesis is the truth value of a hypothesis that is accepted or rejected. Because the value of t arithmetic> t table 3,832> 1,916, then H0 is rejected and Ha is accepted or "there is an Effect of Entrepreneurship Subjects on Entrepreneurial Interest in SMA Negeri 1 Sungai Ambawang" Keywords: Entrepreneurship Subjects, Entrepreneurial Interes